2014
DOI: 10.3917/spub.145.0715
|View full text |Cite
|
Sign up to set email alerts
|

Les modalités de collecte du financement de la santé au Burkina Faso de 1980 à 2012

Abstract: As a step towards universal health coverage, African countries need to develop funding systems that are effective, equitable, and tailored to national circumstances. To support policy makers in Burkina Faso, we present a review of research on interventions related to user fees, prepayment plans, and user fee subsidies. We compiled a narrative summary of articles published in scientific journals between 1980 and 2012. In all, 64 articles were selected. A thematic analysis was performed. User fees are a barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
(131 reference statements)
0
5
0
1
Order By: Relevance
“…Even though this study’s findings regarding health expenses and services use are limited because of our small sample, they nevertheless highlight, once more, the challenges of healthcare accessibility and the financial burden these can generate [ 49 ]. There have been numerous studies in Burkina Faso on these issues [ 50 ], but again, none have looked specifically at dengue. Such studies have yet to be conducted in Africa [ 49 ], with particular attention on equity issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this study’s findings regarding health expenses and services use are limited because of our small sample, they nevertheless highlight, once more, the challenges of healthcare accessibility and the financial burden these can generate [ 49 ]. There have been numerous studies in Burkina Faso on these issues [ 50 ], but again, none have looked specifically at dengue. Such studies have yet to be conducted in Africa [ 49 ], with particular attention on equity issues.…”
Section: Discussionmentioning
confidence: 99%
“…In Cambodia, for example, studies have revealed the extent to which families become indebted to cover expenses related to dengue episodes [ 51 ], and the overall financial burden for society and its economy is enormous [ 52 ]. The fact that Burkina Faso’s health system is still based on user fees means there is an important financial barrier to healthcare access [ 50 ]. New dengue epidemics could exacerbate these impacts for families, especially for the poorest, as was clearly demonstrated in Cambodia [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the aim of the present study was to deepen our understanding of the “black box” of PBF, taking Burkina Faso as a case study. In Burkina Faso, the achievement of UHC continues to be compromised by insufficient health funding and poor health system performance [ 21 ], with child and maternal mortality rates among the highest globally [ 22 ]. The situation prompted the Ministry of Health (MOH) to undertake a PBF intervention through a World Bank(WB)-supported project, as a trial project in three districts first in 2011 and since 2014 under the form of a three-year pilot project.…”
Section: Introductionmentioning
confidence: 99%
“…Le fait que la plupart des premiers auteurs des articles tirés de ces partenariats soient situés dans des institutions du Nord est source de débat [28]. Notre analyse des articles parus depuis 30 ans concernant le financement de la santé au Burkina Faso montre que les chercheurs du pays ne sont premiers auteurs que dans 5% des articles auxquels ils participent [29]. Cette question devient importante puisque la collaboration scientifique internationale est en croissance.…”
Section: La Conduite Responsable En Contexte De Collaboration Internationaleunclassified